On the Uniqueness of Limit Cycles in Codimension Two Bifurcations (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper we present a survey on the uniqueness of limit cyclesbifurcating from a center, homoclinic loop or a heterclinic loop in planar systems, introducing five bifurcation theorems, and then apply the theorems tothe study of codimension two bifurcations, obtaining a complete analysis onthe uniqueness of limit cycles.
Keywords: Uniqueness; limit cycle; bifurcation; codimension two.